Cardiac and respiration induced motion of mediastinal lymph node targets in lung cancer patients throughout the radiotherapy treatment course. Issue 1 (October 2016) - Schmidt, Mai Lykkegaard; Hoffmann, Lone; Knap, Marianne Marquard; Rasmussen, Torben Riis; Folkersen, Birgitte Holst; Toftegaard, Jakob; Møller, Ditte Sloth; Poulsen, Per Rugård
Abstract: Background and purpose: Involved mediastinal lymph nodes (LNs) are often included in the radiotherapy target for lung cancer patients. Their motion may differ from the primary tumor motion, possibly undermining the loco-regional control. This study determines the detailed differential target motion throughout the treatment course. Material and methods: Ten lung cancer patients with 2–4 fiducial markers implanted in LN targets received IMRT with a daily pre-treatment cone-beam CT (CBCT) scan. Offline, the 3D trajectory of the markers was determined from their projected trajectory in the CBCT projections. Frequency analysis was performed to separate the intrafraction motion into a respiratory and cardiac component. The mean setup error of the markers and the motion range were used to calculate margins required for LN targets when setup is based on soft-tissue match. Results: Respiration motion was largest in the CC direction and more prominent for more caudal LNs. Cardiac motion was often (73%) largest in the AP direction and tended to be largest for more cranial LNs. Margins for intrafraction motion and daily baseline shifts of LNs were 4.8 mm (LR), 6.0 mm (CC) and 6.7 mm (AP). Conclusions: Detailed mapping showed that LN motion was in general governed by breathing, but some LNs had substantial cardiac induced motion.